MELACAK TERM KORUPSI DALAM AL-QUR’AN SEBAGAI EPISTEMOLOGI PERUMUSAN FIKIH ANTIKORUPSI - Syaiful Ilmi (Khatulistiwa, 2011)
Corruption is an incessant discourse that continues to go through the dynamics. It also triggers a more comprehensive interpretation of corruption, and no exception in this case the Qur'an. In concrete, the Qur'an does not mention the term corruption as an explicit legal entity, but rather certain terms such as ghulul, al-suht, al-dawl and hirabah which lead to of the substance of corruption. Departing from these terms, a framework for the formulation of anti-corruption jurisprudence began to be discussed as a form of epistemology of prevention and its eradication.